Alphaviruses in Cancer Therapy - Lundstrom, Kenneth (Frontiers in Molecular Biosciences, 2022)
Alphaviruses have been engineered as expression vectors for different strategies of cancer therapy including immunotherapy and cancer vaccine development. Administration of recombinant virus particles, RNA replicons and plasmid DNA-based replicons provide great flexibility for alphavirus applications. Immunization and delivery studies have demonstrated therapeutic efficacy in the form of reduced tumor growth, tumor regression and eradication of established tumors in different animal models for cancers such as brain, breast, colon, cervical, lung, ovarian, pancreas, prostate cancers, and melanoma. Furthermore, vaccinated animals have showed protection against challenges with tumor cells. A limited number of clinical trials in the area of brain, breast, cervical, colon prostate cancers and melanoma vaccines has been conducted. Particularly, immunization of cervical cancer patients elicited immune responses and therapeutic activity in all patients included in a phase I clinical trial. Moreover, stable disease and partial responses were observed in breast cancer patients and prolonged survival was achieved in colon cancer patients.